(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This article studies the influence of the speed of a car with low and ultra-low profile tires, 14ʹʹ and 16ʹʹ, negotiating a turn through an interactive software system developed by us in the MATLAB environment. The changes of the normal and lateral loads of the wheels are obtained and the characteristics of the side slip angle (known as side slip) of the pneumatic tires are determined. Taking into account the side slip of the wheels, the software determines the center of the turn. The characteristics for the normal and lateral loads and of the side slip of the wheels for both types of tires are given. The influence of the tire profile on the handling characteristics is analysed. Recommendations are proposed for a personal car’s motion in a turn with both types of tires.